CLONING, EXPRESSION PATTERNS, AND PRELIMINARY CHARACTERIZATION OF AccCPR24, A NOVEL RR‐1 TYPE CUTICLE PROTEIN GENE FROM Apis cerana cerana. Issue 3 (2nd October 2013) - Chu, Xiaoqian; Lu, Wenjing; Zhang, Yuanying; Guo, Xingqi; Sun, Rujiang; Xu, Baohua
<x xml:space="preserve">Abstract</x> Cuticular proteins (CPs) are key components of insect cuticle, a structure that plays a pivotal role in insect development and defense. In this study, we cloned the full‐length cDNA of a CP gene from Apis cerana cerana (AccCPR24). An amino acid sequence alignment indicated that AccCPR24 contains the conserved Rebers and Riddiford consensus sequence and shares high similarity with the genes from other hymenopteran insects. We then isolated the genomic DNA and found that the first intron, which is present in other CP genes, is absent in AccCPR24. Real‐time quantitative polymerase chain reaction (qPCR) analysis revealed that AccCPR24 is highly expressed in the late pupal stage and midgut. Expression was inhibited by an exogenous ecdysteroid in vitro but was enhanced by this hormone in vivo; environmental stressors, such as heavy metals and pesticides, also influenced gene expression. In addition, a disc diffusion assay showed that AccCPR24 enhanced the ability of bacterial cells to resist multiple stresses. We infer from our results that AccCPR24 acts in honeybee development and in protecting these insects from abiotic stresses.